Complex Steel Structures : Non-Orthogonal Geometries in Building with Steel - Meyer Boake, Terri (Birkhäuser, 2020)
Complexity in architecture, construction and material manipulation is constantly increasing due to our present ability to design, calculate and fabricate an extending range of geometric shapes and systems. This volume addresses the design of complexity in the planning, fabrication and construction of steel structures based on non-orthogonal geometries: curved and chaotic geometries, poly-diagrid systems, lattice-grid structures and others. Topical photographs by the author on a wide range of international projects present innovative methods and techniques, providing an excellent understanding of the possibilities and requirements of complex steel structures.